2019
DOI: 10.1038/s41598-019-40861-7
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic optical power dropouts driven by low frequency bias forcing in a mid-infrared quantum cascade laser

Abstract: Mid-infrared quantum cascade lasers operating under external optical feedback and external periodic bias forcing are shown to exhibit a deterministic chaotic pattern composed of frequencies which are linked to the one of the forcing. Results also show that both the amplitude and the frequency of the forcing play a key role in the number of retrieved spikes per modulation period. These findings are of paramount importance for chaotic operation of quantum cascade lasers in applications such as optical countermea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…These are, to the best of our knowledge, the first results reporting on the nonlinear dynamics of QCLs emitting right in the transparency window between 8.5 µm and 11 µm. Similar results with a Type 1 QCL have already been reported [38]. Fig.…”
Section: Spiking Dynamics Under Current Modulationsupporting
confidence: 90%
See 1 more Smart Citation
“…These are, to the best of our knowledge, the first results reporting on the nonlinear dynamics of QCLs emitting right in the transparency window between 8.5 µm and 11 µm. Similar results with a Type 1 QCL have already been reported [38]. Fig.…”
Section: Spiking Dynamics Under Current Modulationsupporting
confidence: 90%
“…The higher the frequency, the lower the number of spikes and the lower the amplitude, the lower the number of spikes. Other results with a Type 1 QCL showed that the value of the continuous pump that is applied prior to the periodic modulation has very small influence on the number of spikes per period [38]. If the periodic forcing is not a sine wave but a square wave, like shown in Fig.…”
Section: Spiking Dynamics Under Current Modulationmentioning
confidence: 92%
“…In this case, the chaotic dropouts synchronize with the periodic modulation, and the number of spikes per periods can vary through a modification of the amplitude of the modulation or the frequency of the modulation. 28 Analyzing the spiking dynamics showed that some configurations led to spikes with a magnified amplitude. The amplitude of these spikes is very sensitive to any change of the parameters, as shown in In this configuration, the amplitude of the modulation corresponds to 28% of the pumping current.…”
Section: Extreme Events In Qclsmentioning
confidence: 99%
“…20 This chaotic pattern is composed of intensity dropouts, called low-frequency fluctuations (LFFs), and experiments showed that an extensive control of these spikes was possible under a periodic excitation. 28 In this work, we experimentally build up a nonlinear dynamical setup to show the first extreme events emitted by a mid-infrared QCL operating under external feedback. In addition to that, we also describe several methods to trigger those events with a maximum success rate of 47%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation